Penanaman Pendidikan Karakter Melalui Pembuatan Video Bertema Cinta Tanah Air - Ratino Ratino; Darojat Darojat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to explain the cultivation of character education through making videos with the theme of love for the country. Love for one's country involves elements of loyalty, appreciation and concern for the nation. Character education, especially love of the country, needs to be implemented from an early age in a fun way, one of which is in the form of videos. This is also an answer to challenges and technological developments. Students are not only provided with theory, but practical and meaningful learning through video making projects. The results of making the video show the diversity of students in expressing their love for their country. These results show that students are able to adapt to the latest science and technology by applying various latest applications on their devices.